THE EFFECT OF DATE JUICE AND HONEY ON INCREASING HEMOGLOBIN IN PREGNANT WOMEN WITH ANEMIA - Alfiah Rahmawati; Rr Catur Leny Wulandari; Atika Zahria Arisanti; Alivia Nurrokhmah (International Islamic Medicine Forum, 2022)
Pregnancy is a physiological change in women. There are changes in the body during pregnancy, one of which is in the blood vessel system. These changes make the volume of plasma in the blood increase, this results in dilution of the blood. From these changes, pregnant women are prone to anemia, where the condition of the body lacks blood. Globally, the incidence of anemia reaches 29.9% in women of childbearing age or more than half a billion women aged 15-49 years have anemia. With a prevalence of 29.6% in non-pregnant women of childbearing age and 36.5% in pregnant women of childbearing age. Anemia in pregnancy has several effects such as premature birth and postpartum hemorrhage. So anemia during pregnancy requires serious treatment. There are pharmacological and non-pharmacological treatments for anemia. One of the non-pharmacological treatments that can be done is using dates and honey. Dates and honey contain iron, vitamin C, vitamin B complex and folic acid which are needed in the formation of blood cells. In this case, the researcher conducted a search for evidence of foreign literature traced through electronic media facilities with keyword guidance. There were 6 relevant articles, each of which represented an effect of giving dates and honey in cases of anemia during pregnancy, especially in pregnant women who have anemia.